InDels within caprine IGF2BP1 intron 2 and the 3′‐untranslated regions are associated with goat growth traits. (17th October 2019) - Wang, Z.; Zhang, X.; Jiang, E.; Yan, H.; Zhu, H.; Chen, H.; Liu, J.; Qu, L.; Pan, C.; Lan, X.
Summary: Insulin‐like growth factor 2 mRNA binding protein 1 (IGF2BP1) is involved in the Hedgehog pathway and has been shown to regulate the RNA stability of several growth‐related target genes. It is located in a quantitative trait locus showing a strong association with traits related to body size in ducks. Fibroblast growth factor receptor 1 (FGFR1) also participates in Hedgehog signaling pathways and has been reported to be associated with organic growth and development. FGFR1 ‐knockout mice have been shown to have severe postnatal growth defects, including an approximately 50% reduction in body weight and bone mass. Meanwhile, nonsense‐mediated mRNA decay factor (SMG6) can maintain genomic stability, which is associated with organic growth and development. Therefore, we hypothesized that IGF2BP1, FGFR1 and SMG6 genes may play important roles in the growth traits of goats. In this study, the existence of two insertion/deletion (InDel) variants within IGF2BP1, one InDel within FGFR1 and two InDels within SMG6 was verified and their correlation with growth traits was analyzed in 2429 female Shaanbei white cashmere goats. Results showed both the 15 bp InDel in intron 2 and the 5 bp InDel in the 3′ regulatory region within IGF2BP1 were significantly associated with growth traits ( P  <   0.05) and goats with the combinatorial homozygous insertion genotypes of these two loci had the highest body weight ( P  =   0.046). The other InDels within FGFR1 and SMG6 were not obviously associated with growth traits ( P  >   0.05). Therefore, the two InDels in IGF2BP1 were vital mutations affecting goat growth traits.